2022
DOI: 10.3934/jimo.2021008
|View full text |Cite
|
Sign up to set email alerts
|

A unified analysis for scheduling problems with variable processing times

Abstract: This paper considers single-machine scheduling problems with variable processing times, in which the actual processing time of a job is a function of its additional resources, starting time, and position in a sequence. Four problems arising from two criteria (a scheduling cost and a total resource consumption cost) are investigated. Under the linear and convex resource consumption functions, we provide unified approaches and consequently prove that these four problems are solvable in polynomial time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A future extension is to the group scheduling in the flowshop, parallel machines setting, or two-stage assembly flowshop. Other future research may study extending the group scheduling to scenario-dependent processing times (Wu et al [34][35][36]) or variable processing times (Wang et al [37,38]).…”
Section: Discussionmentioning
confidence: 99%
“…A future extension is to the group scheduling in the flowshop, parallel machines setting, or two-stage assembly flowshop. Other future research may study extending the group scheduling to scenario-dependent processing times (Wu et al [34][35][36]) or variable processing times (Wang et al [37,38]).…”
Section: Discussionmentioning
confidence: 99%
“…Under a convex resource consumption function, they provided a bicriteria analysis for the total weighted flow (completion) time and the total resource consumption cost. Wang et al [28] investigated single-machine resource allocation scheduling with learning and deterioration effects. Under the linear and convex resource consumption functions, they provided unified approaches and showed that four versions of the scheduling cost and total resource consumption cost are solvable in polynomial time.…”
mentioning
confidence: 99%
“…Under CONW, SLKW, and DIFW assignments, we showed that these problems can be solved in polynomial time. Further extensions are addressing the above problems in the setting of flow shop and identical (unrelated) parallel machines, considering scheduling with resource-dependent processing times (Wang et al [26], and Wang et al [27]), or studying multitasking scheduling (Xiong et al [30]).…”
mentioning
confidence: 99%